Consolation Without Religious Topoi: Thematic Analysis of References to "Afterlife" in Secular Eulogies in Communist Czechoslovakia (1948-1989) - Svačinová, Iva (Omega, 2025)
The article focuses on practice of secular eulogistic rhetoric in communist Czechoslovakia (1948-1989), specifically it investigates references to "afterlife" used in eulogies, which is generally conceived as allowing the bereaved to positively reappraise the death of the loved one. However, in secular eulogies, the use of "afterlife" in religious interpretation ("resurrection", "heaven") is explicitly excluded. Based on the thematic analysis of 61 secular eulogies, 2 secular interpretations of "afterlife" are identified: symbolic continuity (continuity of memory of the deceased, through his/her legacy/work done, as a part of Nature, through children/future generations, or continuity of the deceased's love) and factual (but deprived) continuity (death is presented as a sleep, journey, or pain relief).
Keywords: Czechoslovakia; postoj ke smrti; ztráta blízké osoby; afterlife; Humans; secular eulogy; Československo; Religion and Psychology; Secularism; dějiny 20. století; Czech Republic; History, 20th Century; sekularismus; mužské pohlaví; Česká republika; consolation; funeral rhetoric; Bereavement; náboženství a psychologie; ženské pohlaví; Attitude to Death; lidé; komunismus; Communism; Male; Female